Pyrrolidines and piperidines bearing chiral tertiary alcohols by nickel-catalyzed enantioselective reductive cyclization of N-alkynones. Issue 1 (December 2018) - Liu, Guodu; Fu, Wenzhen; Mu, Xingye; Wu, Ting; Nie, Ming; Li, Kaidi; Xu, Xiaodong; Tang, Wenjun
Abstract Pyrrolidines and piperidines are important building blocks in organic synthesis. Numerous methods exist for constructing substituted pyrrolidines and piperidines. However, efficient syntheses of pyrrolidines and piperidines bearing chiral tertiary alcohols are limited. Here we report an efficient enantioselective nickel-catalyzed intramolecular reductive cyclization ofN -alkynones. A P-chiral bisphosphorus ligand DI-BIDIME is designed and applied in the synthesis of tertiary allylic siloxanes bearing pyrrolidine and piperidine rings in high yields and excellent enantioselectivities, with triethylsilane as reducing reagent. The highest turn over number achieved is 1000 (0.1 mol% catalyst loading) with > 99:1 er. This reaction provides a practical way to synthesize pyrrolidine and piperidine derivatives with chiral tertiary alcohols from easily accessible starting materials under mild conditions. The products can be scaled up and transformed to various useful chiral intermediates. The P-chiral bisphosphorus ligand developed in this study represents one of the few ligands for highly enantioselective cyclization of alkynones. Transition metal-catalyzed cyclization of alkynes and carbonyls offers a useful route to cyclic allylic alcohols, but typically uses precious metal catalysts. Here, enantioselective nickel-catalyzed reductive cyclization ofN -alkynones gives tertiary allylic alcohols in up to 99:1 er with catalyst loadings of 0.1 mol%